2022
DOI: 10.1002/smll.202203432
|View full text |Cite
|
Sign up to set email alerts
|

Fluorous‐Tagged Peptide Nanoparticles Ameliorate Acute Lung Injury via Lysosomal Stabilization and Inflammation Inhibition in Pulmonary Macrophages

Abstract: Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a common respiratory critical syndrome that currently has no effective therapeutic interventions. Pulmonary macrophages play a principal role in the initiation and progression of the overwhelming inflammation in ALI/ARDS. Here, a type of fluorous‐tagged bioactive peptide nanoparticle termed CFF13F is developed, which can be efficiently internalized by macrophages and suppress the excessive expression of cytokines and the overproduction of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…CFF was conjugated with Tag 1 via the disulfide linkage and the conjugate was further assembled to form peptide nanoparticles ( Figure 2 ). [ 42 ] The nanoparticles were efficiently delivered into bone marrow‐derived macrophages, and inhibited lipopolysaccharide (LPS)‐induced inflammation and reactive oxygen species (ROS) in the treated cells. Transcriptomic results showed that the nanoparticle treatment influenced multiple signal pathways related to inflammation including the TLR signaling pathway, and also inhibited the expression of genes involved in NF‐ κ B and MAPK pathways.…”
Section: Fluorous Tags For Cytosolic Peptide Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…CFF was conjugated with Tag 1 via the disulfide linkage and the conjugate was further assembled to form peptide nanoparticles ( Figure 2 ). [ 42 ] The nanoparticles were efficiently delivered into bone marrow‐derived macrophages, and inhibited lipopolysaccharide (LPS)‐induced inflammation and reactive oxygen species (ROS) in the treated cells. Transcriptomic results showed that the nanoparticle treatment influenced multiple signal pathways related to inflammation including the TLR signaling pathway, and also inhibited the expression of genes involved in NF‐ κ B and MAPK pathways.…”
Section: Fluorous Tags For Cytosolic Peptide Deliverymentioning
confidence: 99%
“…CFF was conjugated with Tag 1 via the disulfide linkage and the conjugate was further assembled to form peptide nanoparticles (Figure 2). [42] The nanoparticles were efficiently delivered into bone marrow-derived macrophages, and inhibited Fluorous tagged CFF peptide for the treatment of LPS-induced acute lung injury. Reproduced with permission.…”
Section: Fluorous Tags For Cytosolic Peptide Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…[33,34] Notably, the high affinity of F─F interactions enables the synthesis of fluoroustagged peptides, which could self-assemble into nanoparticles for efficient intracellular peptide delivery. [35,36] Overall, the selfassembly behavior of fluorocarbon chains shows great potential for nanostructure preparation and drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%